Axillary reverse mapping with indocyanine green or isosulfan blue demonstrate similar crossover rates to radiotracer identified sentinel nodes. Issue 3 (11th December 2017) - Foster, Deshka; Choy, Nicole; Porter, Catherine; Ahmed, Shushmita; Wapnir, Irene
Abstract : Background: Sentinel lymph node (SLN) resection is imperative for breast cancer staging. Axillary reverse mapping (ARM) can preserve arm draining nodes and lymphatics during surgery. ARM is generally performed with isosulfan blue (ISB), restricting its use for concurrent SLN biopsy. Indocyanine green (ICG) could serve as an alternative to ISB for ARM procedures. Methods: SLN mapping and biopsy was performed via periareolar injection of 99 technetium‐sulfur colloid ( 99m TcSc, TSC). ISB and ICG were injected in the upper arm. Blue‐stained lymphatics or nodes were visualized in the axilla; ICG was identified using the SPY Elite ® system. Results: Twenty‐three patients underwent SLN biopsy with or without axillary node dissection and ARM procedures. Twenty of these patients had at least one hot node; 12 patients had SLNs that were only hot, 6 hot/blue/fluorescent, and 2 hot/fluorescent. Overall, crossover of ARM agents with SLNs occurred in 8 cases. Inspection of the axillary cavity after SLN biopsy revealed fluorescent lymphatics and nodes remaining in 14 and 7 patients, respectively. Blue lymphatics and blue nodes were detected in fewer cases. Conclusion: Nearly one‐third of patients showed crossover between breast and arm draining nodes, which provides insight as to why some patients develop lymphedema symptoms after SLN biopsy. ICG and ISB identify similar numbers of SLNs. As such ICG could substitute for ISB in ARM procedures.